Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan Terhadap Ketepatan Pelaporan Keuangan Pada Perusahaan Manufaktuf Sub Sektor Makanan dan Minuman Yang Terdaftar Di bursa Efek Indonesia Periode 2016-2019 - Muhammad Rizki Mubarok; Rilla Gantino (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2021)
This study aims to determine the effect of profitability, liquidity and firm size on the timeliness of financial reporting. The data in this study are secondary data and data obtained from the Indonesia Stock Exchange and company performance reports. The sampling technique used the saturated sample technique with a total sample of 76 observational data from manufacturing companies in the food and beverage sector in 2016-2019. The data analysis technique used multiple linear regression analysis. The results of this study indicate that the variables of profitability, leverage, liquidity simultaneously have an effect on firm value. The leverage variable has no effect on the timeliness of financial reporting, the liquidity variable has no significant effect on the timeliness of financial reporting and the profitability variable has a significant positive effect on the timeliness of financial reporting.